2007
DOI: 10.1038/sj.npp.1301498
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Administration to Aged Male Mice Increases Anti-Anxiety Behavior and Enhances Cognitive Performance

Abstract: Although androgen secretion is reduced with aging, and may underlie decrements in cognitive and affective performance, the effects and mechanisms of androgens to mediate these behaviors are not well understood. Testosterone (T), the primary male androgen, is aromatized to estrogen (E(2)), and reduced to dihydrotestosterone (DHT), which is converted to 5alpha-androstane, 3alpha, 17beta-diol (3alpha-diol). To ascertain whether actions of the neuroactive metabolite of T, 3alpha-diol, mediates cognitive and affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
94
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(104 citation statements)
references
References 81 publications
10
94
0
Order By: Relevance
“…High testosterone is associated with feelings of vigor and activation (Dabbs, Strong, & Milun, 1997;Sherwin, 1988), and testosterone is an effective antidepressant in clinical populations with very low or absent endogenous testosterone production (e.g., Rabkin, Wagner, & Rabkin, 1996). Elevation in testosterone also reduces defensive (fear) responses in a number of species (e.g., Boissy & Bouissou, 1994;Frye, Edinger, & Sumida, 2008;Vandenheede & Bouissou, 1993). An attentional bias for fearful faces (which relates to elevations in fear and anxiety) diminishes after administration of testosterone; conversely, attentional bias for angry faces has been linked with both higher levels of approach motivation (e.g., BAS scores and anger) and higher testosterone (for review, see van Honk & Schutter, 2007).…”
Section: Testosteronementioning
confidence: 99%
“…High testosterone is associated with feelings of vigor and activation (Dabbs, Strong, & Milun, 1997;Sherwin, 1988), and testosterone is an effective antidepressant in clinical populations with very low or absent endogenous testosterone production (e.g., Rabkin, Wagner, & Rabkin, 1996). Elevation in testosterone also reduces defensive (fear) responses in a number of species (e.g., Boissy & Bouissou, 1994;Frye, Edinger, & Sumida, 2008;Vandenheede & Bouissou, 1993). An attentional bias for fearful faces (which relates to elevations in fear and anxiety) diminishes after administration of testosterone; conversely, attentional bias for angry faces has been linked with both higher levels of approach motivation (e.g., BAS scores and anger) and higher testosterone (for review, see van Honk & Schutter, 2007).…”
Section: Testosteronementioning
confidence: 99%
“…We have previously demonstrated that testosterone levels of intact aged male mice (plasma =∼0.4±0.1 hippocampus =∼0.3±0.1 ng/g) are similar to those observed in young, gdx mice (plasma =∼0.3±0.3 ng/ml, hippocampus =∼0.4±0.1 ng/g vs. young, intact male mice plasma =∼2.7±1.5 ng/ml, hippocampus =∼1.0±0.3 ng/g) [15]. Aged female mice have levels in the hippocampus of E 2 (∼2.0±1.0 ng/g) and the P 4 metabolite, 5α-pregnan 3α-ol-20-one (3α,5α-THP; ∼2.0±0.5 ng/g) that are more similar to young diestrous (E 2 ∼10.0±3.0 ng/g; 3α,5α-THP ∼0.7±0.5 ng/g) than to young proestrous mice (E 2 ∼40.5±8.1 ng/g; 3α,5α-THP ∼19.4±4.6 ng/g) [12,13].…”
Section: Animals and Housingmentioning
confidence: 99%
“…There was a main effect of P 4 (F(1,9) = 15.10, P = 0.004), but not sex (F(1,9) = 2.03, P = 0.19), and no interaction (F(1,9) = 2.72, P = 0.13). Young control mice typically have latencies of 40-50 s to crossover to the dark, shock-associated side of the chamber in this task [11,15].…”
Section: Rotarodmentioning
confidence: 99%
See 1 more Smart Citation
“…Conditioned Fear was modified from previously described methods (Frye, Edinger, & Sumida, 2008). Mice were habituated to the conditioning chamber for 4 min.…”
Section: Conditioned Contextual/cued Fearmentioning
confidence: 99%